0
$\begingroup$

I'm working through some problems in an old linear algebra textbook, just brushing up on a few things. I came across an exercise that's been giving me some trouble. The exercise states,

Find the characteristic equation and the real eigenvalues of the matrix $A=\begin{bmatrix} 4 & 0 & -1 \\ 0 & 4 & -1 \\ 1 & 0 & 2 \\ \end{bmatrix} $.

My attempted solution:

$$ A - \lambda I= \begin{bmatrix} 4 & 0 & -1 \\ 0 & 4 & -1 \\ 1 & 0 & 2 \\ \end{bmatrix} - \begin{bmatrix} \lambda & 0 & 0 \\ 0 & \lambda & 0 \\ 0 & 0 & \lambda \\ \end{bmatrix} = \begin{bmatrix} 4 - \lambda & 0 & -1 \\ 0 & 4 - \lambda & -1 \\ 1 & 0 & 2 - \lambda \\ \end{bmatrix} \\ $$ From here we calculate $|A-\lambda I|$ $$ \begin{align} |A-\lambda I| &= (4-\lambda)^2(2-\lambda)-(4-\lambda) \\ & =(\lambda^2-8\lambda+16)(2-\lambda)-(4-\lambda) \\ & =(2\lambda^2-16\lambda+32-\lambda^3+8\lambda^2-16\lambda)-(4-\lambda) \\ & =-\lambda^3+10\lambda^2-32\lambda+32-(4-\lambda) \\ & =-\lambda^3+10\lambda^2-31\lambda+28 \\ \end{align} $$ So, unless I've made errors in my calculations, the characteristic polynomial is $-\lambda^3+10\lambda^2-31\lambda+28$ and the characteristic equation is $-\lambda^3+10\lambda^2-31\lambda+28=0$.

This is where I'm stuck. I haven't had to find the roots of a cubic polynomial in over a decade. I know the quadratic function is used to find the roots of a polynomial with form $ax^2+bx+c=0$. So I looked for a cubic type of quadratic function and found The Cubic Formula, which seems overly complicated.

I believe the roots can be found using $(4-\lambda)^2(2-\lambda)-(4-\lambda)$ but I am unsure of how to go about it. I've been searching for a method but I haven't found one, can someone pleases shed some light on my problem.

$\endgroup$
3
$\begingroup$

Your approach is fine, but not your computations. The characteristic polynomial of $A$ is $-\lambda^3+10\lambda^2-33\lambda+36$. Using the rational root theorem, you can see that its roots are $3$ (twice) and $4$.

By the way, note that the characteristic polynomial is not $(4-\lambda)^2(2-\lambda)-(4-\lambda)$. In fact, it is $(4-\lambda)^2(2-\lambda)+(4-\lambda)$, and\begin{align}(4-\lambda)^2(2-\lambda)+(4-\lambda)&=(4-\lambda)\bigl((4-\lambda)(2-\lambda)+1\bigr)\\&=(4-\lambda)(\lambda^2-6\lambda+9)\\&=(4-\lambda)(\lambda-3)^2.\end{align}

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Oh I see, that makes things very clear. I see that I made an error calculating the determinant. Thank you for also showing how to combine terms in the polynomial to get to $(4-\lambda)(\lambda-3)^2$. $\endgroup$ – Jonny Henly Jun 22 '18 at 15:31
  • 1
    $\begingroup$ @JonnyHenly I'm glad I could help. $\endgroup$ – José Carlos Santos Jun 22 '18 at 15:33
2
$\begingroup$

Even before constructing the characteristic polynomial, you can see from the matrix itself that $(0,1,0)^T$ is an eigenvector with eigenvalue $4$. However, if you didn’t happen to spot this before plunging in, computing the determinant in a different way would have also given you this partial factorization right away: The second column only has one nonzero element, so it’s a prime candidate for computing the determinant. If you expand along the second column, you get $$(4-\lambda)\left((4-\lambda)(2-\lambda)+1\right) = (4-\lambda)(9-6\lambda+\lambda^2) = (4-\lambda)(3-\lambda)^2$$ for the characteristic polynomial.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.